Iodine deficiency among Italian children and adolescents assessed through 24-hour urinary iodine excretion. Issue 4 (15th April 2019) - Campanozzi, Angelo; Rutigliano, Irene; Macchia, Paolo E; De Filippo, Gianpaolo; Barbato, Antonio; Iacone, Roberto; Russo, Ornella; D'Angelo, Giuseppina; Frigeri, Monica; Pensabene, Licia; Malamisura, Basilio; Cecere, Gaetano; et al.
ABSTRACT: Background: Iodine is an essential micronutrient for intellectual development in children. Information on iodine intakes based on 24-h urinary iodine excretion (UIE) is scant, because iodine status is only assessed by the measurement of urinary iodine concentration (UIC) in spot urine samples. Objectives: The aim of our study was to evaluate the iodine intake of school-age children and adolescents, using UIE measurement in 24-h urine collections. Methods: The study population included 1270 healthy subjects (677 boys, 593 girls) aged 6–18 y (mean age ± SD: 10.3 ± 2.9) from 10 Italian regions. Daily iodine intake was estimated as UIE/0.92, based on the notion that $\sim$ 92% of the dietary iodine intake is absorbed. The adequacy of intakes was assessed according to the Dietary Reference Values for iodine of the European Food Safety Authority (EFSA). Body mass index (BMI) and UIC were also measured for each subject. Results: Based on the scientific opinion of EFSA, 600 of 1270 subjects (47.2%) had a lower than adequate iodine intake, with a higher prevalence among girls (54.6%) compared with boys (40.2%) ( P  < 0.001). Although UIE and 24-h urinary volumes increased with age ( P  < 0.001), a progressive decrease in the percentage of subjects with iodine excretion <100 µg/24 h ( P  < 0.001) was observed, without any significant difference in the percentage of subjects with UIC <100 µg/L. No significant association was detected between BMI z -score and UIE ( P  = 0.603) or UIC ( P  = 0.869). Conclusions: A sizable proportion of our population, especially girls, appeared to be at risk of iodine inadequacy. The simple measurement of UIC could lead to underestimation of the occurrence of iodine deficiency in younger children, because of the age-related smaller urine volumes producing spuriously higher iodine concentrations.